Characterising hyperinsulinemia-induced insulin resistance in human skeletal muscle cells. (April 2020) - Turner, Mark C; Martin, Neil R W; Player, Darren J; Ferguson, Richard A; Wheeler, Patrick; Green, Charlotte J; Akam, Elizabeth C; Lewis, Mark P
Abstract : Hyperinsulinaemia potentially contributes to insulin resistance in metabolic tissues, such as skeletal muscle. The purpose of these experiments was to characterise glucose uptake, insulin signalling and relevant gene expression in primary human skeletal muscle-derived cells (HMDCs), in response to prolonged insulin exposure (PIE) as a model of hyperinsulinaemia-induced insulin resistance. Differentiated HMDCs from healthy human donors were cultured with or without insulin (100 nM) for 3 days followed by an acute insulin stimulation. HMDCs exposed to PIE were characterised by impaired insulin-stimulated glucose uptake, blunted IRS-1 phosphorylation (Tyr 612 ) and Akt (Ser 473 ) phosphorylation in response to an acute insulin stimulation. Glucose transporter 1 (GLUT1), but not GLUT4, mRNA and protein increased following PIE. The mRNA expression of metabolic ( PDK4 ) and inflammatory markers ( TNF-α ) was reduced by PIE but did not change lipid ( SREBP1 and CD36 ) or mitochondrial ( UCP3 ) markers. These experiments provide further characterisation of the effects of PIE as a model of hyperinsulinaemia-induced insulin resistance in HMDCs.